The thermo-mechanical behavior of brake discs for high-speed railway vehicles - Hong, Heerok; Kim, Minsoo; Lee, Hoyong; Jeong, Naktak; Moon, Hyunguk; Lee, Eunseong; Kim, Hyungmin; Suh, Myungwon; Chung, Jongduk; Lee, Junghwan (Journal of mechanical science and technology, 2019)
The structure of a brake disc is coupled to the axle and rotates together with the wheel. A brake disc is a friction-type device that presses the pad on both sides of the disc. As more of its surface area becomes exposed to the air, it has better heat dissipation than the drum disc. It also has low fade phenomenon or vapor lock phenomenon despite frequent brake operation. In addition, it has the advantage of enabling precise control. But the braking force is obtained by the disc brake system by using the frictional force between the disc and the pad, and the pad is subjected to wear. For high-speed railway vehicles in particular, the wear and tear of the pad occurs more rapidly. This not only shortens the replacement cycle of the pad, but also has the disadvantage of reducing braking efficiency due to the rise in temperature during the initial braking process. Moreover, the heat that occurs will cause thermal distortion, which leads to the occurrence of a hot spot. This results in a reduction of the disc life. Looking comprehensively at the research trends to date it appears that thermal behavior analysis has only been performed thus far in terms of frictional thermal energy between the disc and the pad. Thermomechanical contact characteristics, on the other hand, have yet to be considered. The thermal behavior of the disc is analyzed experimentally using an infrared camera, and the causes of the hot band and hotspot are suggested. This analytical approach can shorten the analysis time, but it can only confirm the temperature distribution achieved by a single braking. While there is a significant difference in temperature distribution according to the actual braking, the analytical approach has solely focused on the hotspot generation mechanism. Therefore, in this study, the authors will use both a dynamometer and a thermographic camera to analyze BPs through a repetitive braking process, and will attempt to verify the cause of thermomechanical movement and BP occurrence through contact analysis of the disc and the pad.